Development of multiaxial warp knitting technology for production of three-dimensional near net shape shell preforms. Issue 10 (June 2017) - Sankaran, Vignaesh; Rittner, Steffen; Hahn, Lars; Cherif, Chokri
The possibility of direct preforming in the near net shape of final component structure with load- and shape-conforming fiber orientations is highly essential in composite production, not only to reduce costs but also to attain better mechanical properties and form stability. Based on the concept of varying the reinforcement yarn lengths during the feed-in (warp yarn delivery) and segmented doffing, synchronous working numerically controlled warp yarn delivery and doffing machine modules have been newly developed for multiaxial warp knitting machines to create a resource efficient textile process chain by a single-step, large-scale oriented production of load- and form-conforming warp knitted three-dimensional shell preforms with free-form geometrical surfaces. Such customized preforms in the near component net shape offer higher material utilization and increased lightweight potential.